Non-linear model order reduction for elastohydrodynamic lubrication simulations of polymer seals. (December 2019) - Ischinger, F.; Bartel, D.; Brunk, M.; Solovyev, S.
Abstract: In the field of elastohydrodynamic lubrication (EHL) simulations, the importance of considering non-linearities in the structure increases constantly. In most cases, the finite element method is used to discretize the non-linear continuum equations. Apart from this, model order reduction techniques are used in EHL simulations to decrease the number of unknowns and the computational time. However, the reduction methods typically used are limited to linear problems. The aim of this paper is to introduce a model order reduction technique to EHL simulations, that captures non-linear behavior. As an example, a hyperelastic 2D axially symmetric seal is reduced and coupled to the Reynolds equation. The simulation is accelerated by a factor of 10 and beyond while the non-linear properties are preserved. Highlights: Introduction of a non-linear model order reduction to EHL simulations with reduction of structural part and fluid coupling. Comparison of reduced model with full order FEM discretization for a lubricated polymer seal in large areas of non-linearity. Efficient generation of the reduced model by using uncoupled structural mechanical precomputations in a commercial FEM tool. Computational speed-up of a factor of 10 and beyond due to the reduction.